Virtual drag and drop using open CV And Arduino - Fridjat, AbdelFattah; Aliat, Boubakeur; Imad, Nattari (Echahid Hama Lakhdar University of Eloued, 2023)
"Summary : Virtual drag and drop technology using Open CV and Arduino is one of the innovative technologies in the field of computer vision and electronic interaction. This technology allows users to drag and drop digital elements onto the screen using hand gestures. This technology is based on a connection between a computer and an Arduino board and using the Open CV library for image processing and hand movement analysis. A camera is used to capture the movement of the hand and locate it on the screen. Arduino receives the signals sent from the computer and performs the actions required to achieve the drag-and-drop operation." "ملخص: تقنية السحب والإفلات الافتراضية باستخدام CV Open و Arduino هي إحدى التقنيات المبتكرة في مجال رؤية الكمبيوتر والتفاعل الإلكتروني. تتيح هذه التقنية للمستخدمين سحب العناصر الرقمية وإفلاتها على الشاشة باستخدام إيماءات اليد. تعتمد هذه التقنية على اتصال بين جهاز كمبيوتر ولوحة Arduino وتستخدم مكتبة CV Open لمعالجة الصور وتحليل حركة اليد. تستخدم الكاميرا لالتقاط حركة اليد وتحديد موقعها على الشاشة. يستقبل Arduino الإشارات التي يرسلها الكمبيوتر ويقوم بالإجراءات اللازمة لأداء عملية السحب والإفلات "
مذكرة ماستر اتصالات Des thèses télécominication
Keywords: Keywords: Open CV, Computer Vision, hand movement, Arduino Python, Virtual drag-and-drop.; الكلمات الرئيسية: السيرة الذاتية، رؤية الكمبيوتر، حركة اليد، Arduino، السحب والإفلات الظاهري